Design of Electrostatic immersion Lens Accelerating Operated Under Zero Magnification Conditions - A. Mohmmed, Intehaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Theoretical study computerized has been carried out in electron optics field, to design electrostatic immersion lens , the inverse problem is important method in the design of electrostatic lenses by suggesting an axial electrostatic potential distribution using polynomial function. The paraxial â€“ray equation is solved to obtain the trajectory particles that satisfy the suggested potential function. In this research, designed immersed lens length L = 10mm operated under zero condition, as it was obtained the electrode shape of this lens solutions using the Laplace equation The results of the search showed low values of spherical and chromatic aberrations, which gives a good indication of the design of the lens.   It was also  drawn the electrodes shape of the lens two-dimensional and three dimensions through the use of simulation software, known as (Simion7)